1990
DOI: 10.1016/0014-5793(90)80704-m
|View full text |Cite
|
Sign up to set email alerts
|

ATP synthesis coupled to electron transfer from H2 to the heterodisulfide of 2‐mercaptoethanesulfonate and 7‐mercaptoheptanoylthreonine phosphate in vesicle preparations of the methanogenic bacterium strain Gö1

Abstract: Crude vesicle preparations of the methano8enic strain Go1 were able to couple the reduction of the heterodisulfide of 2-mercaptoetbanesulfonate and 7-mercaptoheptanoylthreonine phosphate (CoM-99HTP) by H, with ATP formation. The rate of ATP synthesis was 1 mol/min mg protein. ATP synthesis and disulfide reduction were only observed with CoM-S-S-HTP, but not with CoM-4S-CoM or HTP-S-S-HTP. The methylreductase inhibitor 2-brorn~~~~ulfo~cacid had no effect on ATP synthesis induced by CoM-S-4HTP reduction with Hr.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
20
0

Year Published

1990
1990
2018
2018

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(20 citation statements)
references
References 13 publications
0
20
0
Order By: Relevance
“…Redox titrations were performed by the methods of Dutton (9) and Wilson (39) in a customdesigned cuvette (path length, 1 cm; Ochs, Bovenden, Germany) at 25°C. Redox potentials were measured with a micro-redox-electrode type Pt 5700 A (combination electrode; Schott, Hofheim, Germany) in the presence of the following redox mediators: 2,6-diaminodurol (Em7 = +260 mV), 33 ,uM; 1,2-naphthoquinone (Em 7 = +143 mV), 34 ,uM; phenazine methosulfate (Em7 = +80 mV), 18 ,uM; phenazine ethosulfate (Em 7 = +55 mV), 16 ,uM; duroquinone (Em,7 = +5 mV), 33 ,uM; pyocyanine (Emn7 = -34 mV), 4 R,M; 2,3-dimethyl-1,4-naphthoquinone (Em 7 = -80 mV), 83 ,uM; 2-hydroxy-1,4-naphthoquinone (Em;7 -152 mV), 31 ,uM; anthraquinone-2,6-disulfonate (Em 7 = -184 mV), 18 ,uM; anthraquinone-2-sulfonate (Em 7 = -224 mV), 18 ,uM; phenosafranine (Em 7 = -252 mV), 0.23 ,uM; acridinium chloride (Em,7 = -313 mV), 19 ,uM; diquat (Em7 = -349 mV), 5 ,uM; methylviologen (Em 7 = -449 mV), 0.4 ,uM. To obtain a fast response, the platinum electrode was activated by successive incubations in hydroquinone (in 40 mM sodium oxalate buffer, pH 4.0) and Na2SO3 (in H20) followed by sandpapering prior to each titration.…”
Section: Growthmentioning
confidence: 99%
See 1 more Smart Citation
“…Redox titrations were performed by the methods of Dutton (9) and Wilson (39) in a customdesigned cuvette (path length, 1 cm; Ochs, Bovenden, Germany) at 25°C. Redox potentials were measured with a micro-redox-electrode type Pt 5700 A (combination electrode; Schott, Hofheim, Germany) in the presence of the following redox mediators: 2,6-diaminodurol (Em7 = +260 mV), 33 ,uM; 1,2-naphthoquinone (Em 7 = +143 mV), 34 ,uM; phenazine methosulfate (Em7 = +80 mV), 18 ,uM; phenazine ethosulfate (Em 7 = +55 mV), 16 ,uM; duroquinone (Em,7 = +5 mV), 33 ,uM; pyocyanine (Emn7 = -34 mV), 4 R,M; 2,3-dimethyl-1,4-naphthoquinone (Em 7 = -80 mV), 83 ,uM; 2-hydroxy-1,4-naphthoquinone (Em;7 -152 mV), 31 ,uM; anthraquinone-2,6-disulfonate (Em 7 = -184 mV), 18 ,uM; anthraquinone-2-sulfonate (Em 7 = -224 mV), 18 ,uM; phenosafranine (Em 7 = -252 mV), 0.23 ,uM; acridinium chloride (Em,7 = -313 mV), 19 ,uM; diquat (Em7 = -349 mV), 5 ,uM; methylviologen (Em 7 = -449 mV), 0.4 ,uM. To obtain a fast response, the platinum electrode was activated by successive incubations in hydroquinone (in 40 mM sodium oxalate buffer, pH 4.0) and Na2SO3 (in H20) followed by sandpapering prior to each titration.…”
Section: Growthmentioning
confidence: 99%
“…The methanogenic pathways leading to the conversion of these substrates have been unraveled in the last two decades, and they involve a number of unique cofactors (37). The penultimate step of methanogenesis, the reduction of the heterodisulfide of coenzyme M and 7-mercaptoheptanoylthreonine phosphate (CoM-S-S-HTP) with either H2 or reduced coenzyme F420 (F420H2) as a reductant, was shown in Methanosarcina strain Gol to be coupled to electron transport phosphorylation (7,34 Membrane preparations. For the spectroscopic and potentiometric characterization of cytochromes, membranes were prepared under aerobic conditions.…”
mentioning
confidence: 99%
“…CH3-S-CoM + HTP-SH CH4 + CoM-S-S-HTP [4] CoM-S-S-HTP + H2 CoM-SH + HTP-SH [5] Experimental evidence was provided that the reduction of the heterodisulfide (CoM-S-S-HTP) (reaction 5) might be the actual energy-conserving reaction (14).…”
mentioning
confidence: 99%
“…The reduction of CoM-S-S-COB with H, (Peinemann et al, 1990;Deppenmeier et al, 1991) and F,,,H, (Deppenmeier et al, 1990) has been shown to be coupled with energy conservation via the chemiosmotic mechanism (Deppenmeier et al, 1996).…”
mentioning
confidence: 99%